2008
DOI: 10.1254/jphs.fp0072035
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Gabexate Mesilate–Induced Cell Injury in Porcine Aorta Endothelial Cells

Abstract: Abstract. Gabexate mesilate (GM), a serine protease inhibitor, often causes severe vascular injury, when injected in high concentration. In the present study, we investigated the mechanisms for the cytotoxicity of GM on porcine aorta endothelial cells (PAECs). GM (0.5 -5.0 mM) decreased cell viability in a dose-dependent manner and caused cell injury, whilst nafamostat mesilate (NM), another serine protease inhibitor, or mesilate itself had no effect on cell viability. zVAD-fmk, a pancaspase inhibitor, or zDEV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…We previously reported that GM induced cellular membrane injury immediately after treatment with GM, suggesting that GM induces necrotic cell death via injury of the cell membrane (5). In the present study, we found that Gly completely suppressed the GM-induced increase in PI uptake.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…We previously reported that GM induced cellular membrane injury immediately after treatment with GM, suggesting that GM induces necrotic cell death via injury of the cell membrane (5). In the present study, we found that Gly completely suppressed the GM-induced increase in PI uptake.…”
Section: Discussionsupporting
confidence: 74%
“…Taken together with these findings, our results suggest that several amino acids such as Gly protect against GM-induced endothelial cell injury. In addition, we previously reported that mannitol, a regulatory drug of osmotic pressure, had no effect on the GM-induced cell injury (5). Therefore, it is unlikely that osmotic pressure is involved in the protective effects of amino acids.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…These observations were in agreement with the marked lag between the time of intravenous infusion and the subsequent appearance of vascular injury in patients receiving intravenous infusion of NIC. Wallin et al reported that the symptoms of vascular injuries tended to increase over 14 hr in patients receiving intravenous infusion of NIC (Aki et al, 2008). These findings suggest that monitoring the infusion site 12 hr after injection might contribute to early detection and rapid cure.…”
Section: Morphological Changes Of Nic-exposed Hmvecmentioning
confidence: 98%